2022
DOI: 10.31648/oej.8551
|View full text |Cite
|
Sign up to set email alerts
|

Analiza podobieństwa sytuacji makroekonomicznej i poziomu inwestycji w Unii Europejskiej w latach 2018-2020 w kontekście pandemii Covid-19

Abstract: The purpose of this article was to determine the macroeconomic and investment situation in 2018-2020 in the Member States of the European Union. The work also deals with the division of the European Union into three parts: the core, the periphery, and  Central and Eastern Europe. A critical analysis of the scientific literature was used to present the economic consequences of the pandemic. Ward's method was used to create a few clusters of European Union Member States that are most similar to each other in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Investments are a significant component of the process of shaping economic conditions (Nowak & Ryć 2002;Próchniak & Rapacki 2012). Furthermore, the recent years of the COVID-19 pandemic have demonstrated that the macroeconomic and investment situation in many countries, including the EU member states, has deteriorated and that there are still considerable disproportions between groups of countries in terms of their development and economy (Pukin & Markowski, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Investments are a significant component of the process of shaping economic conditions (Nowak & Ryć 2002;Próchniak & Rapacki 2012). Furthermore, the recent years of the COVID-19 pandemic have demonstrated that the macroeconomic and investment situation in many countries, including the EU member states, has deteriorated and that there are still considerable disproportions between groups of countries in terms of their development and economy (Pukin & Markowski, 2022).…”
Section: Introductionmentioning
confidence: 99%